Evaluation of Implementation of Massachusetts Sports Concussion Regulations: Results of Focus Groups With School Nurses and Athletic Trainers. (October 2018) - Howland, Jonathan; Hackman, Holly; Taylor, Alyssa; Brown, Linda; Gapinski, Mary Ann; Mills, Julie Kautz; Thornton, Kathleen
In 2015, the Massachusetts Department of Public Health conducted focus groups with school nurses (SNs) and athletic trainers (ATs) from Massachusetts middle and high schools to assess implementation of legislated regulations relative to the management of students' head injuries incurred during extracurricular sports. Four tape-recorded focus groups were conducted by experienced facilitators. Lists of themes were synthesized by investigators for each focus group. Participating SNs and ATs supported the sports concussion legislation, felt that implementation had gone well, indicated that the law empowered them in managing return-to-school/play for students with concussion, and experienced support from their school administrators. Some SNs reported that they had applied relevant procedures to all students with head injuries, regardless of how or where the injury occurred. Challenges identified included protocols for away games, inconsistent concussion care by physicians, and a need for teacher education. Further research is required to quantify these findings.